10 mJ single-frequency, injection-seeded Q-switched Er:YAG laser pumped by a 1470 nm fiber-coupled LD. (16th January 2018) - Gao, C Q; Shi, Y; Ye, Q; Wang, S; Na, Q X; Wang, Q; Gao, M W
Abstract: A 1645 nm injection-seeded Q-switched Er:YAG laser resonantly pumped by a 1470 nm fiber-coupled laser diode is demonstrated with a non-planar ring oscillator as a seed laser to realize the single-frequency operation. The maximum output pulse energy of the laser is 10.1 mJ, corresponding to a pulse width of 205 ns at a repetition rate of 200 Hz. The half-width of the pulse spectrum is 2.44 MHz measured by a heterodyne technique. The fluctuation of the center frequency of the pulsed laser is 1.43 MHz (RMS) in 1 h. To the best of our knowledge, this is highest energy obtained from a single-frequency, injection-seeded Er:YAG laser pumped by a laser diode.